Identification and antimicrobial susceptibility of referred Nocardia isolates in Victoria, Australia 2009–2019. Issue 8 (17th August 2022) - Yeoh, Kim; Globan, Maria; Naimo, Phillip; Williamson, Deborah A.; Lea, Kerrie; Bond, Katherine
Abstract : Introduction. Nocardia is an opportunistic pathogen that can cause significant morbidity and mortality, particularly in the immunocompromised host. Antimicrobial susceptibility profiles vary across Nocardia spp. and vary within Australia as well as worldwide. Knowledge of local susceptibility patterns is important in informing appropriate empiric antimicrobial therapy. Gap Statement. This is the largest study to date in Australia that correlates antimicrobial susceptibility profiles with molecular identification of Nocardia species. It is the first study that examines isolates from multiple institutions across the state of Victoria, Australia. Aim. To investigate the species distribution and antibiotic susceptibility of Nocardia spp. isolates referred to the Mycobacterial Reference Laboratory (MRL) in Victoria, Australia from 2009 to 2019. Methodology. We conducted a retrospective review of Nocardia spp. isolates which were identified using molecular sequencing. Antimicrobial susceptibility testing was performed using standardized broth microdilution method with Sensititre RAPMYCO1 plates. Species distribution and antibiotic susceptibility profiles were analysed. Results. In total, 414 Nocardia isolates were identified to 27 species levels, the majority originating from the respiratory tract ( n =336, 81.2 %). N. nova ( n =147, 35.5 %) was the most frequently isolated, followed by N. cyriacigeorgica ( n =75, 18.1 %). Species distribution varied by isolate source, with N. farcinica and N. paucivorans found more commonly from sterile sites. Linezolid and amikacin had the highest proportion of susceptible isolates (100 and 99% respectively), while low susceptibility rates were detected for ceftriaxone (59 %) and imipenem (41 %). Susceptibility to trimethoprim sulfamethoxazole varied by species (0–100 %). Conclusion. This is the largest study to date in Australia of Nocardia species distribution and antimicrobial susceptibility patterns. N. farcinica and N. paucivorans were more likely to be isolated from sterile sites, while N. brasiliensis and N. otitidiscvarium were more likely to be isolated from skin and soft tissue. First line therapeutic antimicrobial recommendations by local guidelines were not necessarily reflective of the in vitro susceptibility of Nocardia isolates in this study, with high susceptibility detected for linezolid and amikacin, but poor susceptibility demonstrated for ceftriaxone and imipenem. Profiles for trimethoprim-sulfamethoxazole varied across different Nocardia species, warranting ongoing susceptibility testing for targeted clinical use.